Type II Secretion Is Essential for Virulence of the Emerging Fish Pathogen, Hypervirulent Aeromonas hydrophila - Barger, Priscilla C.; Liles, Mark R.; Newton, Joseph C. (Frontiers in Veterinary Science, 2020)
Hypervirulent Aeromonas hydrophila (vAh) is an emerging pathogen in freshwater aquaculture systems. In the U.S.A., outbreaks of motile aeromonad septicemia associated with vAh result in the loss of over 3 million pounds of catfish from Southeastern production systems each year. A. hydrophila is a well-known opportunistic pathogen that secretes degradative and potentially toxigenic proteins, and the rapid mortality that occurs when catfish are challenged with vAh by intraperitoneal injection suggests that vAh-induced motile aeromonad septicemia may be, in part, a toxin-mediated disease. While vAh isolates from carp isolated in China possess complete Type I, Type II, and Type VI secretion systems, many of the US catfish isolates only possess complete Type I and Type II secretions systems. In order to determine the role of secreted proteins in vAh-induced disease, and to determine the extent of protein secretion by the Type II secretion pathway, an exeD secretin mutant was constructed using a recombineering method in the well-characterized vAh strain A. hydrophila ML09-119. Wild-type and mutant secretomes were analyzed for protein content by SDS-PAGE and by assays for specific enzymes and toxins. Type II secretion-deficient mutants had a near complete loss of secreted proteins and enzyme/toxin activity. The intact Type II secretion system was cloned and used to complement the deletion mutant, ML09-119 exeD, which restored protein secretion and the degradative and toxigenic potential. In vivo challenges in channel catfish resulted in complete attenuation of virulence in ML09-119 exeD, while the complemented mutant was observed to have restored virulence. These results indicate that secreted proteins are critical to vAh virulence, and that the Type II secretion system is the primary secretory pathway utilized for multiple effectors of vAh pathogenesis.